Statistical Properties of Pc4‐5 ULF Waves in Plasmaspheric Plumes - Zhaoyang Lu; Jingchun Li; Shuai Zhang; Alexander W. Degeling; Chao Shen; Jiaqi Dong; Quanqi Shi; Anmin Tian (Geophysical Research Letters, 2024)
Abstract Ultra‐low‐frequency (ULF) waves emerge as pivotal factors in elucidating the mechanisms that drive the intricate dynamics of radiation belt electrons within the plasmasphere and plasmaspheric plumes. Utilizing THEMIS data from September 2012 to September 2017, we conducted a comprehensive statistical analysis of Pc4‐5 ULF waves within and outside the plasmaspheric plume. Our findings reveal a distinctive dawn‐dusk asymmetry in occurrence rate and wave power of poloidal mode waves in the absence of the plume, resembling the toroidal mode asymmetry observed. Poloidal mode waves exhibit a higher likelihood of formation within the plume, while the toroidal mode waves show the opposite trend, contributing to the elevated dusk‐side occurrence rate of poloidal mode waves. Moreover, both wave modes within the plume demonstrate lower peak frequencies compared to waves outside the plume. The global distribution of wave power within the plume suggests higher power at noon than on the dusk side.